2015 IEEE 14th International Conference on Machine Learning and Applications (ICMLA) 2015
DOI: 10.1109/icmla.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

An Edge-Less Approach to Horizon Line Detection

Abstract: Abstract-Horizon line is a promising visual cue which can be exploited for robot localization or visual geo-localization. Prominent approaches to horizon line detection rely on edge detection as a pre-processing step which is inherently a non-stable approach due to parameter choices and underlying assumptions. We present a novel horizon line detection approach which uses machine learning and Dynamic Programming (DP) to extract the horizon line from a classification map instead of an edge map. The key idea is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 26 publications
0
38
0
1
Order By: Relevance
“…Both machine learning based edge-less [4] and edge-based [3] approaches outperform the classical edge-based approach [5] by a high margin (see Table I). A quick look of table I reveals that edge-based method [3] outperforms edge-less approach [4]. To better understand the strengths and weaknesses of each method, we present below several reasons.…”
Section: Fusionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both machine learning based edge-less [4] and edge-based [3] approaches outperform the classical edge-based approach [5] by a high margin (see Table I). A quick look of table I reveals that edge-based method [3] outperforms edge-less approach [4]. To better understand the strengths and weaknesses of each method, we present below several reasons.…”
Section: Fusionmentioning
confidence: 99%
“…Although the full DCSI can be used for horizon line detection, it was found that keeping only the m highest classification scores in each column does not compromise accuracy while reduces computations. The reduced DCSI is referred to as mDCSI [4]. The multi-stage graph corresponding to the mDCSI contains less vertices; as a result, fewer paths need to be considered when searching for the shortest path which results in considerable speedups.…”
Section: Edge-less Horizon Line Detectionmentioning
confidence: 99%
See 3 more Smart Citations